Tetrabromobisphenol A Promotes the Osteoclastogenesis of RAW264.7 Cells Induced by Receptor Activator of NF-kappa B Ligand In Vitro - Park, So Young; Choi, Eun Mi; Suh, Kwang Sik; Kim, Hyun-Sook; Chin, Sang Ouk; Rhee, Sang Youl; Kim, Deog-Yoon; Oh, Seungjoon; Chon, Suk (Journal of Korean medical science, 2019)
Tetrabromobisphenol A (TBBPA), one of the most widely used brominated flame-retardants, is a representative persistent organic pollutants group. Studies on TBBPA toxicity have been conducted using various target cells; however, few studies have investigated TBBPA toxicity in bone cells. Therefore, this study investigated the in vitro effects of TBBPA on osteoclasts, a cell type involved in bone metabolism. RAW264.7 cells were cultured in medium containing 50 ng/mL receptor activator of nuclear factor kappa B ligand (RANKL) and varying concentrations of TBBPA. To evaluate the effects of TBBPA on the differentiation and function of osteoclasts, osteoclast-specific gene expression, tartrate-resistant acid phosphatase (TRAP) activity, bone resorbing activity, mitochondrial membrane potential (MMP) and mitochondrial superoxide were measured. The presence of 20 μ TBBPA significantly increased TRAP activity in RANKL-stimulated RAW264.7 cells, the bone resorbing activity of osteoclasts, and the gene expression of Akt2, nuclear factor of activated T-cells cytoplasmic 1, and chloride channel voltage-sensitive 7. However, TBBPA treatment caused no change in the expression of carbonic anhydrase II, cathepsin K, osteopetrosis-associated transmembrane protein 1, , extracellular signal-related kinase, , , or matrix metalloproteinase 9. Furthermore, 20 μ TBBPA caused a significant decrease in MMP and a significant increase in mitochondrial superoxide production. This study suggests that TBBPA promotes osteoclast differentiation and activity. The mechanism of TBBPA-stimulated osteoclastogenesis might include increased expression of several genes involved in osteoclast differentiation and reactive oxygen species production.